Answer:
the log of the first equation gives the second
Explanation:
You want to know why ...
![\displaystyle 2^(16^x)=16^(2^x)](https://img.qammunity.org/2023/formulas/mathematics/college/aj87v3cbxrgpxxklv324fw29y5o3cjxmzc.png)
means ...
![16^x=4\cdot2^x](https://img.qammunity.org/2023/formulas/mathematics/college/pd6qnzhe40oyxi8yurvt7wiit77l6si3rm.png)
Logarithms
Taking logs to the base 2 of the original equation, we get ...
![16^x=(2^x)\log_2{16}\\\\\boxed{16^x=4\cdot2^x}](https://img.qammunity.org/2023/formulas/mathematics/college/zrtey2lloqox999ijickrufnoiirji6jec.png)
__
Additional comment
This is the relation you asked about. It can be solved by taking logs one more time (base 2).
4x = 2 +x
3x = 2 . . . . . . . subtract x
x = 2/3 . . . . . . . divide by 3
This is the only value of x for which all of these exponential expressions have the relations given.
The relevant log relation is ...
log(a^b) = b·log(a)